Pluralizm religijny wyzwaniem dla wczesnej edukacji - Aniela Różańska (Problemy Wczesnej Edukacji)
In the article the question of religious pluralism is presented. The author gives the characteristics of this concept, which has changed its meaning over the recent years. The author brings into light some contemporary ways of perception of the religious pluralism and controversies they result in. The concept of inclusive pluralism by Jacques Dupuis has been recommended by the author as a model of religious pluralism which enables the opening of religious education on the inter-religious dimension. A proper understanding of religious pluralism plays an important role in forming an open religious identity which is one of the key tasks in education including early education.